2019
DOI: 10.1097/sla.0000000000002600
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Resectability and Survival in Patients With Borderline and Locally Advanced Pancreatic Cancer who Underwent Neoadjuvant Treatment With FOLFIRINOX

Abstract: BR/LA PDAC patients with no progression on neoadjuvant FOLFIRINOX should be offered surgical exploration. Except size, traditional pathological parameters fail to predict survival among resected FOLFIRINOX patients. Resected FOLFIRINOX patients have survival that appears to be superior than that of resectable patients who go directly to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
229
3
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(267 citation statements)
references
References 23 publications
10
229
3
10
Order By: Relevance
“…Generally, an upfront surgical approach has not been justified in patients with UR‐PDAC due to the high frequency of mortality and morbidity and poor prognosis. Conversion surgery provided favorable outcomes of a high proportion of margin‐negative resection and negative lymph node metastasis, resulting in improved MST ranging from 19.5 to 64 months in patients with initial UR‐PDAC . When patients were selected after a favorable response to anticancer treatment followed by conversion surgery, MST did not seem to differ according to resectability status.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, an upfront surgical approach has not been justified in patients with UR‐PDAC due to the high frequency of mortality and morbidity and poor prognosis. Conversion surgery provided favorable outcomes of a high proportion of margin‐negative resection and negative lymph node metastasis, resulting in improved MST ranging from 19.5 to 64 months in patients with initial UR‐PDAC . When patients were selected after a favorable response to anticancer treatment followed by conversion surgery, MST did not seem to differ according to resectability status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on CS among patients with UR‐PC have been reported so far . In the most recent meta‐analysis based on reports since 2009, the rate of conversion from UR‐LA disease to surgery was 26% and OS was 18.7 months .…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent meta‐analysis based on reports since 2009, the rate of conversion from UR‐LA disease to surgery was 26% and OS was 18.7 months . Other reports of conversion from initial UR‐PC to radical surgery after favorable response to induction treatment reported a wide range of conversion rates, depending on whether patients with M disease were included . Nitsche et al reported that CS was possible in four (28.6%) of 14 patients with UR‐PC who received FOLFIRINOX as first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations